2014
DOI: 10.7314/apjcp.2014.15.20.8855
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Chemotherapy-Related Hyperglycemia on Prognosis of Child Acute Lymphocytic Leukemia

Abstract: Purpose: To investigate the impact of hyperglycemia during inductive treatment on the prognosis of acute lymphocytic leukemia (ALL) in children. Materials and Methods: Clinical data of 159 ALL childhood cases were reviewed. The patients were divided into the hyperglycemia group (fasting glucose≥126mg/dl and/or random blood glucose≥200mg/dl) and the euglycemia group according to the blood glucose values. The Χ2 test was performed to compare the complete remission rates of the two groups, and Kaplan-Meier and lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
29
3
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(38 citation statements)
references
References 18 publications
3
29
3
3
Order By: Relevance
“…Zhang et al had reported that the ALL patients with hyperglycaemia achieved CR lesser than the euglycemic group (86.8% vs. 95%; p-value= 0.134) though not significant. 11 Roberson et al in their study of childhood ALL during remission induction had found that patients with hyperglycaemia during induction were less likely to achieve CR by the end of induction (p-value=0.03). 7 In our study the CR rate was lower in hyperglycaemic group vs. non hyperglycaemic group (87.5% vs 100%; p-value=0.13).…”
Section: Discussionmentioning
confidence: 97%
“…Zhang et al had reported that the ALL patients with hyperglycaemia achieved CR lesser than the euglycemic group (86.8% vs. 95%; p-value= 0.134) though not significant. 11 Roberson et al in their study of childhood ALL during remission induction had found that patients with hyperglycaemia during induction were less likely to achieve CR by the end of induction (p-value=0.03). 7 In our study the CR rate was lower in hyperglycaemic group vs. non hyperglycaemic group (87.5% vs 100%; p-value=0.13).…”
Section: Discussionmentioning
confidence: 97%
“…(1) • According to sex, there was a statistically significant difference between the two subgroups (p-value 0.001) as shown in table (2). • As regarding blood sugar level in the studied groups there was a significant relationship between group I and group II as shown in table (3) • Also, there was significant relationship between the two subgroups as shown in tables (4) and (5) and the ratio of patients developed hyperglycemia to euglycemia was 33 (30.3%) to 76(69.7%) • According to CBC parameters the study showed significant relationship between patients with white blood cell count ≥20×10 9 /L and patients with white blood cell count <20×10 9 /L in group IIa and group IIb at the end of the induction period on the 33rd day with no significance in other CBC parameters on the other hand, peripheral blood juvenile cells at diagnosis were >5%and by comparison between peripheral blood juvenile cells in hyperglycemic and euglycemic cases it showed that there was no significance between the two subgroups on the 8th day of induction treatment but it was significant on 15th day and 33rd day. • Bone marrow aspiration was done at the diagnosis of the 109 patients with ALL and all showed >30% blast cells in bone marrow and by evaluation of bone marrow during the period of induction there was no significant relationship between bone marrow findings at 15th day between the two subgroups but it was significant at 33th P-value < 0.05 as shown in table (7)…”
mentioning
confidence: 79%
“…Taking the incidence of hyperglycemia into consideration (the incidence being between 9,7%-56%; Lowas et al, 2009). Zhang et al, (2014) study has shown association between the incidence of hyperglycemia 5-year overall survival rate and the relapse-free survival rate. To date, there is still no official report available on the incidence rate of hyperglycemia in children with ALL receiving induction phase of chemotherapy in Indonesia.…”
Section: The Effect Of Combination Of Steroid and L-asparaginase On Hmentioning
confidence: 99%